Keefektifan Pembelajaran Kooperatif Tipe CIRC Berbantuan Alat Peraga terhadap Kemampuan Pemecahan Masalah Materi Segiempat - Amalia Fitri (Universitas Pekalongan, 2013)
The research was aimed at first investigating the problem solving of students who were taught with the CIRC method especially within the material of quadrilateral, and second investigating wether the students could reach the competence expected. The results of the research showed that the students taught with CIRC model were better in achieving in competence. In conclusion this model of teaching could be used to improve student’s problem solving skills both for the material of quadrilateral and for other materials having similiar characteristics.